Spin-Charge Conversion Phenomena in Germanium - Oyarzun-Medina, S (Physical Society of Japan, 2017)
The spin-orbit coupling relating the electron spin and momentum allows for spin generation, detection and manipulation. It thus fulfils the three basic functions of the spin field-effect-transistor made of semiconductors. In this paper, we review our recent results on spin-charge conversion in bulk germanium and at the Ge(111) surface. We used the spin pumping technique to generate pure spin currents to be injected into bulk germanium and at the Fe=Ge(111) interface. The mechanism for spin-charge conversion in bulk germanium is the spin Hall effect and we could experimentally determine the spin Hall angle ΘSHE, i.e., the spin-charge conversion efficiency, in heavily doped n-type and p-type germanium. We found very small values at room temperature: ΘSHE ≈ (1-2) × 10-3 in n-Ge and ΘSHE ≈ (6-7) × 10-4 in p-Ge. Moreover, we pointed out the essential role of spin dependent scattering on ionized impurities in the spin Hall effect mechanism. We concluded that the spin Hall effect in bulk germanium is too weak to produce large spin currents, whereas a large Rashba effect (>100 meV) at Ge(111) surfaces covered with heavy metals could generate spin polarized currents. We could indeed demonstrate a giant spin-to-charge conversion in metallic states at the Fe= Ge(111) interface due to the Rashba coupling. We generated very large charge currents by direct spin pumping into the interface states from 20K to room temperature. By this, we raise a new paradigm: The possibility to use the spin-orbit coupling for the development of the spin-field-effect-transistor. © 2017 The Physical Society of Japan.